Reconstruction of Household Furniture Based on the Karmawibhangga Relief of Borobudur Temple - Widayat, Rahmanu; B. Studyanto, Anung (Mudra Jurnal Seni Budaya, 2022)
The development of modern household furniture is currently experiencing rapid expansion. On the other hand, the legacy of ancient household furniture still survives; it can be seen from household furniture in the 9th century through the two-dimensional Karmawibhangga reliefs of Borobudur Temple. To understand the three-dimensional shape from the relief, it is interesting to make a replica of this household furniture. The problem of this study is to understand the form of household furniture found in the reliefs of Borobudur Temple. The method used in this study is identification, reconstruction, and analyzation the value of its benefits. The result is several types of household furniture replicas. The benefits of this study are as a source of inspiration forthe development of modern home furniture designs and also to respect and develop the legacy from the ancestors.